The Effect of Moringa Oliefera (Moringa Oliefera) Leaf Flour Concentration and Duration of Steaming on the Characteristics of Instant Noodles - Desi Utami Desi; Rima Azara (jurnal makanan tropis dan teknologi agroindustri, 2021)
This study aims to determine the effect of Moringa Leaf Flour (Moringa Oliefera) Concentration and Steaming Time on the Characteristics of Instant Noodle (Instant Noodle). This study was conducted using a factorial randomized block design (RAK) with the first factor being the concentration of Moringa leaf flour treatment consisting of 3 levels, namely K1 (6%), K2 (9%), K3 (12%), and steaming time consisting of 3 levels. namely P1 (3 minutes), P2 (5 minutes), P3 (7 minutes). The variables measured were water content, ash content, crude fiber content, physical analysis (swelling index, cooking loss, cooking time, water absorption and color reader method), and organoleptic tests. Moringa leaf flour concentration treatment and steaming time significantly affected the parameters of physical color, moisture content, fiber content, and organoleptic tests (color, aroma, and taste) but had no significant effect on parameters of water absorption, swelling index, cooking loss, cooking time. , ash content, and organoleptic test (texture). The best treatment parameter in this study was Moringa instant noodles with 6% Moringa leaf concentration treatment, 3 minutes steaming time (K1P1) which showed 8.55% moisture content, 8.05% ash content, 11.26% fiber content, lightness value. 48.1, redness value 21.50, yellowness value 33.35, cooking loss value 0.13%, cooking time value 12.07%, water absorption 5.14%, swelling index value 7.09%, and test organoleptic aroma 3.43 (neutral-like), color 4.00 (like-very like), taste 3.53 (neutral-like), and texture 3.57 (neutral-like).